Terminal complexes of the complement system: new structural insights and their relevance to function. Issue 1 (November 2016) - Morgan, Bryan Paul; Walters, David; Serna, Marina; Bubeck, Doryen
Summary: Complement is a key component of innate immunity in health and a powerful driver of inflammation and tissue injury in disease. The biological and pathological effects of complement activation are mediated by activation products. These come in two flavors: (i) proteolytic fragments of complement proteins (C3, C4, C5) generated during activation that bind specific receptors on target cells to mediate effects; (ii) the multimolecular membrane attack complex generated from the five terminal complement proteins that directly binds to and penetrates target cell membranes. Several recent publications have described structural insights that have changed perceptions of the nature of this membrane attack complex. This review will describe these recent advances in understanding of the structure of the membrane attack complex and its by‐product the fluid‐phase terminal complement complex and relate these new structural insights to functional consequences and cell responses to complement membrane attack.